Information Awareness on Nutrition Online of Phra Nakhon Rajabhat University Students - Yamwong, Nonthanun; Pakdee, Weerachart; Saengmaneedech, Thirawut; Panyasim, Patalee (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2025)
Information awareness on nutrition online of Phra Nakhon Rajabhat University students” aimed to study demographic characteristics. Behavioral awareness of nutrition news from social media and nutrition information literacy in social media of Phra Nakhon Rajabhat University students to study the differences of demographic characteristics and nutritional information literacy in social media of Phra Nakhon Rajabhat University students and to study the relationship between nutrition information exposure behavior from social media and nutrition information literacy. This study is quantitative research. using the survey research model Use online questionnaires to collect information. The sample group in this research consisted of 400 students from Phra Nakhon Rajabhat University who were 18 years of age and older who had been exposed to information about nutrition from social media. The general population in Phra Nakhon Rajabhat University students was more female than male. And most of them were in the age range of 18-20 years. At the same time, most of the sample had a bachelor’s degree and studying at the Teacher Training College In addition, most of the samples were exposed to health news from social media, Facebook. During the period most of the sample group was exposed to health news via social media in the period between 6:01 AM - 24:00 PM and often uses a mobile phone or smartphone Most of the respondents were exposed to nutrition content on social media about detox the most. In addition, the sample group was aware of health information on social media at a high level has an average of 3.63